Transforming Public Services under Climate Threats: Integrating Adaptive Social Protection into Minimum Service Standards in Gorontalo Province - Wahyudi Gobel (Journal of Governance and Global Studies, 2026)
Implementation of Minimum Social Service Standards (SPM) at the local level in Indonesia often operates in an ecological vacuum, focusing on administrative checklists and ignoring external ecological shocks. Gorontalo Province faces double pressure: fluctuations in SPM achievement and projected sea level rise (1–5 meters) in 2045–2050 that threaten more than 122,104 vulnerable groups. Objective: This study analyzes the integration of Adaptive Social Protection (PSA) based on micro-spatial risk data into the formulation and funding of regional social services. Methods: Using qualitative-interpretive methodology and policy-deliberative approaches, this study leverages SEPAKAT-DTSEN data and evaluates local institutional frameworks through Moore's Public Value Lens. Results: Findings show that social services are currently highly reactive and structurally isolated from climate mitigation schemes. There are layered vulnerabilities where 243 people with disabilities and 299 elderly people face direct displacement threats without adaptive livelihood diversification. Theoretical Contribution: This study introduces the concept of Eco-Public Value, which expands the theory of public administration by combining the provision of compulsory public services with ecological resilience. Policy Implications: In practical terms, this study offers a strategic roadmap for local governments to develop Adaptive Social Protection Regional Action Plans (RAD PSAs) and optimize alternative financing through state-religious philanthropy collaboration (BAZNAS).